IMPLEMENTATION OF THE INSPIRATIONAL FRIDAY PROGRAM (CHARITY, HEALTH AND CLEANLINESS) AS A STRATEGY FOR HABITUATING STUDENTS CARING CHARACTER IN MADRASAH IBTIDAIYAH - Ni'matus Sholikhah; Dukan Jauhari Faruq (PGMI Fakultas Tarbiyah Universitas Islam Jember, 2026)
The Jum'at Inspiratif Program is a madrasa strategy to foster students' caring character through planned and integrated habituation within school activities. This study aims to describe: (1) planning, (2) implementation, and (3) evaluation of the Jum'at Inspiratif Program in shaping students' caring character. This research employed a qualitative descriptive approach involving the principal, teachers, and students as informants. Data were collected through interviews, observations, and documentation, then analyzed using the Miles and Huberman model through data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The results show that: (1) program planning is in accordance with the madrasa's goals; (2) implementation runs consistently through charity, healthy living, and cleanliness activities involving all school members; and (3) evaluation is conducted through periodic observation of students' behavior and teacher reflection. This program shows changes in students' behavior, which are indicated by the emergence of habits such as giving charity voluntarily, actively maintaining health, and taking care of environmental cleanliness without being reminded. These findings indicate that the Inspirational Friday Program can be one of the strategies to foster caring character among students and has the potential to serve as a model for other madrasahs in developing students' character through structured and sustainable real-life activities.